Profil Klinik Pasien dengan Ulkus Dekubitus di RSUD Dr. Soetomo Surabaya - Huvi, Indira; Saputro, Iswinarno Doso; Murtiastutik, Dwi (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2019)
Decubitus ulcer or known as pressure ulcer is one of the types of chronic wounds that are often found. The incidences of decubitus ulcers are quite high in some countries, including in Indonesia. The main cause of decubitus ulcer is, long term immobilization, as example the total bedrest patients. Decubitus ulcers are associated with some diseases that causes immobilization such as spinal cord injury, lower extremity fracture, stroke, etc. The aim of this research is to identify the data of patients with decubitus ulcer in RSUD Dr. Soetomo period 1 January 2017 ? 31 December 2017. This research is a descriptive retrospective by collecting 148 secondary data from the medical records in RSUD Dr. Soetomo period 1 January 2017 ? 31 December 2017. Decubitus ulcer mostly be found in elderly (>65 years old) and was dominated by women. The most common disease that associated with decubitus ulcer is trauma (spinal cord injury and lower extremity fracture). The onset of decubitus ulcer in RSUD Dr. Soetomo patients is mostly more than 7 days. The prognosis and outcome of patients with decubitus ulcer are mostly dubia, with 2nd degree of ulcer and in alive condition.